2015
DOI: 10.1183/09031936.00134214
|View full text |Cite
|
Sign up to set email alerts
|

Protective role for club cell secretory protein-16 (CC16) in the development of COPD

Abstract: Rationale Club cell secretory protein-16 (CC16) is the major secreted product of airway Club cells, but its role in the pathogenesis of COPD is unclear. We measured CC16 airway expression in humans with and without COPD and CC16 function in a cigarette smoke (CS)-induced COPD mice model. Methods Airway CC16 expression was measured in COPD patients, smokers without COPD, and non-smokers. We exposed wild-type (WT) and CC16-/- mice to CS or air for up to 6 months, and measured airway CC16 expression, pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
169
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(183 citation statements)
references
References 40 publications
13
169
1
Order By: Relevance
“…In a logistic regression model, adjusted for age, sex, Hispanic ethnicity, baseline BMI, pack years, current smoking at baseline and baseline per cent predicted FEV1, CC16 showed a negative association with COPD (OR 0.71, p=0.01; n=313/1210). This is also consistent with our recent findings in mice and humans [5].…”
supporting
confidence: 94%
See 1 more Smart Citation
“…In a logistic regression model, adjusted for age, sex, Hispanic ethnicity, baseline BMI, pack years, current smoking at baseline and baseline per cent predicted FEV1, CC16 showed a negative association with COPD (OR 0.71, p=0.01; n=313/1210). This is also consistent with our recent findings in mice and humans [5].…”
supporting
confidence: 94%
“…Serum CC16 levels are low in cigarette smokers [3] and increase following smoking cessation [4], but patients with chronic obstructive pulmonary disease (COPD) show progressive decrease in CC16 with disease severity [5]. Thus, although the association between circulating levels of CC16 and airflow obstruction is accepted, the association between circulating CC16 and chronic bronchitis, and whether a link in association exists between circulating CC16 levels, lung function decline and chronic bronchitis have not been shown.…”
mentioning
confidence: 99%
“…Serum CC16 level has been shown as a potential biomarker of accelerated lung function decline in a very large cohort [7]. CC16 polymorphism and local deficiency on the one hand, and a decreased number of club cells on the other hand, were reported as features of COPD [8,9], as confirmed by LAUCHO-CONTRERAS et al [10] in the current issue of the European Respiratory Journal. In previous studies, exogenous CC16 showed pharmacological properties that could decrease excess airway inflammation and mucus production in ex vivo models [11][12][13].…”
supporting
confidence: 63%
“…The paper by LAUCHO-CONTRERAS et al [10] has reported novel and important observations of knockout CC16 mice exposed to 6 months of smoking. They not only observed an increased susceptibility of the knockout animals to emphysema and peribronchiolar fibrosis, but also unravelled potential mechanisms of action of CC16 involved in COPD development.…”
mentioning
confidence: 99%
“…While previous studies have demonstrated a relatively stable median CC16 value in normal controls (5‐7 ng/mL),12, 13 the median CC16 value of non‐ARDS patients in this study appeared to be higher (24.13±12.32 ng/mL). Some cases from the non‐ARDS patient group had developed pulmonary diseases such as pneumonia, which may have caused an elevated production of CC16 18. The compromised renal function indicated by an increase of Scr in some non‐ARDS patients may be another reason accounting for the difference in the CC16 levels since a decreased glomerular filtration rate retards the clearance of CC16 19…”
Section: Discussionmentioning
confidence: 99%